PSYCHOLOGICAL AND DIDACTIC FEATURES TEST TEST OF STUDENTS 'KNOWLEDGE IN CONDITIONS PERSONALITY-ORIENTED LEARNING (Pedagogy of Higher and Secondary Education, 2004)
Account of the age psychological particularities of the development schoolboys at period of early adolescence and particularities component composition to educational activity pupils in their senior year with standpoint of the organizations of the checking the knowledge in condition larval-oriented education on example of the test tasks are analyzed in article.